Lexical-grammatical classification of phrasal verbs in japanese language. (Journal of Oriental Studies, 2016)
In the present article is considered about phraseology of Japanese language, the specific and types of phraseology of Japanese language. The authorresearching the phraseology in the Japanese compared with Kazakh one. So she revealed the differences and similarities of the both languages.